Pediatric Mortality in a Rural Tertiary Care Center in Liberia - Carmelle Tsai; Camila B. Walters; John Sampson; Francis Kateh; Mary P. Chang (MDPI AG, 2017)
Liberia is a low‐income country in West Africa that has faced significant challenges, including a civil war and the recent Ebola epidemic. Little data exists on the more current post‐war and pre‐Ebola trends of child health in Liberia in the rural setting. This study is a retrospective chart review of pediatric mortality in 2013 at a rural tertiary care center in Liberia, 10 years post‐war. From January 2013 to December 2013, there were 50 pediatric deaths, or 5.4% of the 920 total pediatric admissions. The most common cause of neonatal death was sepsis, and the most common cause of death under five years of age was malaria. The majority (82.0%) of the deaths were in children under five. Pediatric mortality at this hospital was similar to other reported mortality six years post‐war, and lower than that reported immediately post‐war. Neonatal sepsis and malaria are two significant causes of pediatric mortality in this community and, therefore, further efforts to decrease childhood mortality should focus on these causes.